Peranan Parasitoid dalam Mengendalikan Hama Puru Daun Eukalyptus (Eucalyptus urophylla S.T. Blake) di Bali - Susila, I Wayan; Supartha, I Wayan; Adriyani, Ni Putu Erina Puspita; Utama, I Wayan Eka Karya; Yudha, I Kadek Wisma (Fakultas Pertanian Universitas Udayana, 2024)
The Role of Parasitoids in Controlling Eucalyptus Gall Pests (Eucalyptus urophylla S.T. Blake) in Bali. Eucalyptus spp. is a plant native in Indonesia. Eucalyptus leaves are part of the plant that is harvested and used as industrial raw material. However, a gall attack on eucalyptus leaves resulted in the formation of galls, which resulted in decreased production in eucalyptus plants. Research on the role of parasitoids in controlling eucalyptus leaf weevil pests in Bali aims to determine the types of parasitoids that play a role in controlling eucalyptus leaf gall pests in Bali. This research consists of field research and laboratory research. Field research was carried out at eucalyptus planting centers in Bali. Laboratory research was carried out at the Integrated Pest and Plant Disease Management Laboratory, Agroecotechnology Study Program, Faculty of Agriculture, Udayana University. The research starts from April to October 2022. This research uses a survey method, sampling is carried out at eucalyptus planting locations in Bali. The results of the research found two types of insect pests that cause gall on eucalyptus plants in Bali, namely Ophelimus eucalypti and Ctenarytaina sp., and there are four species of parasitoids that play a role in controlling it. The four parasitoids are Closterocerus chamaelon Girault (Eulophidae), Megastigmus sp (Torymidae), Erytoma sp, Illger (Eurytomidae) and Quadrastichus mendeli Kim & La Salle (Eulophidae), with parasitization rate of 9.70%, 6.25%, 3.02%, and 2.05% respectively. In total, the parasitization rate of the four parasitoids was 21.02%.